Comparative efficacy and tolerability of medications for Attention-Deficit/Hyperactivity Disorder in children, adolescents and adults: a systematic review and network meta-analysis - Cortese, Samuele; Adamo, Nicoletta; Del Giovane, Cinzia; Mohr-Jensen, Christina; Hayes, Adrian J.; Carucci, Sara; Atkinson, Lauren Z.; Tessari, Luca; Banaschewski, Tobias; Coghill, David; Hollis, Chris; Simonoff, Emily; et al. (Lancet, 2018)
Background The benefits and safety of medications for attention-deficit hyperactivity disorder (ADHD) remain controversial, and guidelines are inconsistent on which medications are preferred across different age groups. We aimed to estimate the comparative efficacy and tolerability of oral medications for ADHD in children, adolescents, and adults.